Neutralization of proteases from Bothrops snake venoms by the aqueous extract from Casearia sylvestris (Flacourtiaceae) - Borges, Márcia Helena (2001)
Aqueous extract from Casearia sylvestris leaves, a typical plant from Brazilian open pastures, was able to neutralize the hemorrhagic activity caused by Bothrops asper, Bothrops jararacussu, Bothrops moojeni, Bothrops neuwiedi and Bothrops pirajai venoms. It also neutralized two hemorrhagic metalloproteinases from Bothrops asper venom. Proteolytic activity on casein induced by bothropic venoms and by isolated proteases, including Bn2 metalloproteinase from B. neuwiedi venom, was also inhibited by the C. sylvestris extract in different levels. The α-fibrinogen chain was partially protected against degradation caused by B. jararacussu venom, when this venom was incubated with C. sylvestris extract. We also observed that this extract partially increased the time of plasma coagulation caused by B. jararacussu, B. moojeni and B. neuwiedi venoms. C. sylvestris extract did not induce proteolysis in any substrate assayed.